2018
DOI: 10.1200/jgo.17.00164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GI Tumor Board on Patient Management and Adherence to Guidelines

Abstract: PurposeAs the burden of cancer on the population and the health care system continues to increase with more complicated treatment options, the need for multidisciplinary teams to be as efficient as possible becomes more vital. Our study aimed to evaluate the consistency of GI Tumor Board (GI TB) recommendations with international guidelines, the adherence of physicians involved in patient care to TB recommendations, and the impact on the management of patients.MethodsA prospective cohort study was conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…[14] In a study on colorectal cancer MTB, discussed cases underwent complete staging studies and had treatment in keeping with established guidelines, increasing compliance from 83% to 98% (p , 0.0001). [25] Similar results were established from lung and esophageal cancer cases discussed in MTBs. [23,26] The frequency of preoperative magnetic resonance imaging scans increased in the MTB cohort and perioperative mortality decreased.…”
Section: Discussionsupporting
confidence: 71%
“…[14] In a study on colorectal cancer MTB, discussed cases underwent complete staging studies and had treatment in keeping with established guidelines, increasing compliance from 83% to 98% (p , 0.0001). [25] Similar results were established from lung and esophageal cancer cases discussed in MTBs. [23,26] The frequency of preoperative magnetic resonance imaging scans increased in the MTB cohort and perioperative mortality decreased.…”
Section: Discussionsupporting
confidence: 71%
“…A study from Botswana showed a reduction in the time from biopsy to start of radiation therapy among patients with cervical cancer [34]. After the implementation of gastro-intestinal MTBs in Saudi Arabia and Ethiopia, adherence to evidence-based guidelines improved [35,36]. Unfortunately, these studies did not provide survival data.…”
Section: Discussionmentioning
confidence: 99%
“…42 Similarly, both a cohort chart review and a prospective observational study respectively revealed change in management in 36% and 25% of gastrointestinal and pancreatic tumors after MTB discussion. 28,43 According to a study on colorectal cancer patients with stage IV disease, recommendations for preoperative chemotherapy have increased significantly in cases of oligometastatic disease (limited to one site) due to input from MTB discussion. Lowes et al observed that after MTB confrontation, physicians were considerably more prone to refer elderly patients (>70 years) for treatment.…”
Section: Improvements In Clinical Decision-making and Patient Managementmentioning
confidence: 99%